Feasibility of sub-dermal soft tissue deformation assessment using B-mode ultrasound for pressure ulcer prevention. Issue 4 (November 2018) - Doridam, J.; Macron, A.; Vergari, C.; Verney, A.; Rohan, P.-Y.; Pillet, H.
Abstract: Pressure Ulcer (PU) prevention remains a main public health issue. The physio-pathology of this injury is not fully understood, and a satisfactory therapy is currently not available. Recently, several works suggested that mechanical strains are responsible of deformation-induced damage involved in the initiation of Deep Tissue Injury (DTI). A better assessment of the internal behavior could allow to enhance the modeling of the transmission of loads into the different structures composing the buttock. A few studies focused on the experimental in vivo buttock deformation quantification using Magnetic Resonance Imaging (MRI), but its use has important drawbacks. In clinical practice, ultrasound imaging is an accessible, low cost, and real-time technic to study the soft tissue. The objective of the present work was to show the feasibility of using B-mode ultrasound imaging for the quantification of localised soft-tissue strains of buttock tissues during sitting. An original protocol was designed, and the intra-operator reliability of the method was assessed. Digital Image Correlation was used to compute the displacement field of the soft tissue of the buttock during a full realistic loading while sitting. Reference data of the strains in the frontal and sagittal planes under the ischium were reported for a population of 7 healthy subjects. The average of shear strains over the region of interest in the fat layer reached levels up to 117% higher than the damage thresholds previously quantified for the muscular tissue in rats. In addition, the observation of the muscles displacements seems to confirm previous results which already reported the absence of muscular tissue under the ischium in the seated position, questioning the assumption commonly made in Finite Element modeling that deep tissue injury initiates in the muscle underlying the bone. Highlights: Development of tissue damage involved in the initiation of DTI is tightly related to localized soft tissue strains. Yet in vivo experimental assessment of localized soft tissue strains in human buttock subdermal tissues during loading never reported. Proposed methodology consists in measuring subdermal soft tissue displacements throughout the full progressive loading of the buttock during sitting motion using B-mode ultrasound imaging in two perpendicular planes and mapping strains using DIC. Results demonstrate the feasibility of in vivo assessment of buttock soft tissue strains during sitting by ultrasound imaging.